"The epic love story of Sam and Dean": "Supernatural," queer readings, and the romance of incestuous fan fiction - Catherine Tosenberger (Transformative Works and Cultures, 2008)
This article examines incestuous slash fan fiction produced for the CW television series Supernatural. I argue that "Wincest" fan fiction is best understood not as perverse, oppositional resistance to a heterosexual, nonincestuous show, but an expression of readings that are suggested and supported by the text itself. I examine the literary, cultural, and folkloric discourses of incest and queerness invoked by the series, paying special attention to Romanticism, the Gothic, and horror as underliers to those discourses, and how those genres inform both the series and the fan fiction. I discuss a number of Wincest stories in detail, focusing upon how these stories build upon thematic elements within the series. In conclusion, I argue that the most resistive aspect of Wincest fan fiction is that it gives the main characters a lasting happiness that the series eternally defers.